Structured Inquiry within a Transdisciplinary Curriculum: Advancing Social Studies Pedagogy in Islamic Schools - Amaliyah, Nurrohmatul; Abdullah, Zuraidah; Omonovich, Khimmataliev Dustnazar; As’ad, Mahrus (Jurnal Pendidikan Islam, 2026)
In an era characterized by rapid social, technological, and environmental transformation, education is increasingly expected to cultivate critical thinking, collaboration, and responsible citizenship rather than mere factual recall. Social Studies education, therefore, requires pedagogical approaches that promote inquiry, conceptual understanding, and interdisciplinary integration. This study examines the implementation of structured inquiry within the International Baccalaureate Primary Years Program (IB-PYP) transdisciplinary framework and its implications for improving Social Studies learning in an Islamic boarding school context. A qualitative classroom action research design was employed in two stages: an exploratory phase conducted in an IB-PYP school and an implementation phase in an Islamic boarding school, where the framework was adapted to the national curriculum. Data were collected through classroom observations, semi-structured interviews, document analysis, and formative assessments across three research cycles. The findings demonstrate progressive improvements in teacher facilitation practices, student engagement, higher-order thinking, and learning outcomes. Inquiry routines gradually became internalized, while transdisciplinary integration enabled students to connect conceptual knowledge with real-life and ethical contexts. The study concludes that structured inquiry embedded within a coherent transdisciplinary framework enhances both cognitive and reflective dimensions of learning. These findings suggest that Islamic educational institutions can effectively integrate global curriculum frameworks to promote holistic, inquiry-oriented, and socially responsible Social Studies education.